Design and microwave-assisted synthesis of a novel Mannich base and conazole derivatives and their biological assessment - Cebeci Yıldız Uygun (De Gruyter, 2021)
4-Amino-5-methyl-2,4-dihydro-3H-1,2,4-triazol-3-one (1) was converted to the corresponding Schiff base (2) by treatment with salicylaldehyde. 1,2,4-Triazoles were then converted to the corresponding Mannich bases containing fluroquinolone core using a one-pot three-component procedure. Moreover, the synthesis of six compounds, which can be considered as conazole analogues, was performed starting from 1,2,4-triazole-3-one compounds via three steps by either conventional or microwave-mediated conditions. All the newly synthesized compounds were screened for their antimicrobial activities. Most exhibited good to moderate antibacterial and/or antifungal activity. The structural assignments of the new compounds were based on elemental analysis and spectral (IR, 1H NMR, 13C NMR, and LC-MS) data.